2015
DOI: 10.1089/dia.2014.0413
|View full text |Cite
|
Sign up to set email alerts
|

A Minority of Patients with Type 1 Diabetes Routinely Downloads and Retrospectively Reviews Device Data

Abstract: Background: In type 1 diabetes (T1D), periodic review of blood glucose and insulin dosing should be performed, but it is not known how often patients review these data on their own. We describe the proportion of patients with T1D who routinely downloaded and reviewed their data at home.Materials and Methods: A cross-sectional survey of 155 adults and 185 caregivers of children with T1D at a single academic institution was performed. “Routine Downloaders” (downloaded four or more times in the past year) were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 30 publications
(35 reference statements)
1
46
3
4
Order By: Relevance
“…The insulin delivery settings for patients starting AP may not be optimized. A well-recognized limitation of current diabetes management is the difficulty in obtaining and analyzing the day-to-day data from diabetes devices, where only a minority of patients ever review their data (28). In fact, during the run-in period of other AP studies, with just the addition of CGM and weekly follow-up for structured education and heightened awareness of their glucose control, patients showed significant improvement in HbA 1c over 4 to 6 weeks before use of AP (29).…”
Section: Resultsmentioning
confidence: 99%
“…The insulin delivery settings for patients starting AP may not be optimized. A well-recognized limitation of current diabetes management is the difficulty in obtaining and analyzing the day-to-day data from diabetes devices, where only a minority of patients ever review their data (28). In fact, during the run-in period of other AP studies, with just the addition of CGM and weekly follow-up for structured education and heightened awareness of their glucose control, patients showed significant improvement in HbA 1c over 4 to 6 weeks before use of AP (29).…”
Section: Resultsmentioning
confidence: 99%
“…It also enables clinicians and diabetes educators to review such data remotely between visits and make more frequent dosing adjustments. Wong et al found that routinely downloading and reviewing glycemic data was associated with a significantly lower HbA1c (7.2% ± 1.0% vs 8.1% ± 1.6%; P = 0.03) . Despite this positive association, they showed that only 31% of adults and 56% of caregivers reported ever downloading data from devices, and even fewer routinely reviewed the downloaded data .…”
Section: Downloading Technologiesmentioning
confidence: 99%
“…Wong et al found that routinely downloading and reviewing glycemic data was associated with a significantly lower HbA1c (7.2% AE 1.0% vs 8.1% AE 1.6%; P = 0.03). 278 Despite this positive association, they showed that only 31% of adults and 56% of caregivers reported ever downloading data from devices, and even fewer routinely reviewed the downloaded data. 278 In a commentary to this article, Beck presented previously unpublished data from the T1DX showing that participants reported rarely or never downloading their devices for BGM (75%), CGM (51%), and insulin pumps (59%).…”
Section: Downloading Technologiesmentioning
confidence: 99%
“…Similarly, in their study aiming to develop an understanding of selfmonitoring of blood glucose in individuals with both type 1 and type 2 diabetes, Fisher, Kohut, Schachner, and Stenger (2011) reported a reduction in the recommended frequency for BG monitoring due to lack of time commitment, whilst participants in the study by Wong, Neistein, Spindler, and Adi (2015) conveyed that a lack of time had an impact on their decision to download and retrospectively review their BG data.…”
Section: Discussionmentioning
confidence: 99%